Efficient and accurate frailty model approach for genome-wide survival association analysis in large-scale biobanks - Rounak Dey; Wei Zhou; Tuomo Kiiskinen; Aki Havulinna; Amanda Elliott; Juha Karjalainen; Mitja Kurki; Ashley Qin; FinnGen; Seunggeun Lee; Aarno Palotie; Benjamin Neale; et al. (Nature Communications, 2022)
The proliferation of large biobanks necessitates statistical methods designed for genetic analysis on biobank data. Here, the authors have developed a frailty model-based method for GWAS analysis of time-to-event phenotypes in large biobanks that accounts for relatedness in samples and censoring of phenotypes.